Sumber-Sumber Motivasi Belajar dari Rumah Peserta Didik Kelas VII - Ogami, Resi; Yosef, Yosef (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
The corona virus pandemic that has hit the world requires everyone to follow health protocols to protect themselves and others from disease transmission. This has also led to many new policies made by the government, especially in education, one of which is a learning system from home for formal education. Education during the pandemic is carried out online, although not all students can learn online effectively because there are various differences in the learning atmosphere compared to the pandemic period, amid the limitations that exist, student still follow the learning which is believed to be driven by various of motivation. This study aims to determine the sources of motivation learning from home of grade VII students at Junior High School 2 Warkuk Ranau Selatan in 2020/2021. This research uses descriptive quantitative method. The data were collected using a questionnaire of sources of motivation learning from home. The populations in this study were students of class VII at Junior High School 2 Warkuk Ranau Selatan in 2020/2021 with a sample size 51 respondents from total population of 103 people. The sampling technique is done through random sampling. The results of the data analysis conducted were 8 students (16%) choose Intrinsik Process Motivation, 11 student (21%) choose Instrumental Motivation, 14 student (28%) choose Eksternal Self-Concept Motivation, 12 student (23%) choose internal self-concept Motivation, and 6 student (12%) choose Goal Internalization. Eksternal self-concept Motivation be the most chosen indicator and Goal Internalization be the least selected indicator.